2022
DOI: 10.1039/d2ra01708c
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the effect of preparation methods on the structural and magnetic properties, and reducibility of CuFe2O4 catalysts

Abstract: The preparation method plays an important role in the structural properties and catalytic performance of CuFe2O4 catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…[ 11 ] The critical inversion parameter for phase transition is believed to be 0.75. [ 19 ] The cation distribution is largely dependent on the synthesis conditions, such as particle size and calcination temperature, [ 11,21–23 ] that appear to have the most significant impact on both structure and degree of inversion. Calculations have shown that the cation distribution significantly affects the electronic properties, with a change from a completely inverted structure to a normal one resulting in a change from semi‐conducting to half‐metallic properties.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 11 ] The critical inversion parameter for phase transition is believed to be 0.75. [ 19 ] The cation distribution is largely dependent on the synthesis conditions, such as particle size and calcination temperature, [ 11,21–23 ] that appear to have the most significant impact on both structure and degree of inversion. Calculations have shown that the cation distribution significantly affects the electronic properties, with a change from a completely inverted structure to a normal one resulting in a change from semi‐conducting to half‐metallic properties.…”
Section: Introductionmentioning
confidence: 99%
“…CuFe 2 O 4 has been used for several catalytic processes, such as methanol steam reforming, [ 22 ] photocatalytic degradation, [ 23 ] photocatalytic water splitting, [ 25 ] photoelectrochemical hydrogen evolution, [ 26 ] photoelectrochemical water oxidation, [ 27,28 ] as well as gas sensor material [ 29 ] or for protein separation. [ 30 ] A huge advantage is the easy recovery of the material due to its magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations